Synthesis and characterizations of Co3O4 based nanocomposite for electrochemical sensor applications / Shahid Mehmood - Shahid , Mehmood (2018)
Cobalt oxide (Co3O4), a metal oxide semiconductor has attained intensive interest and widely investigated due to its extraordinary characteristics such as facile synthetic methodologies, excellent catalytic properties, diverse morphologies and multiple applications. In recent years, enhancing the properties of Co3O4 by incorporating it into a conducting platform such as (in our case) graphene for its viable commercial applications, has been the focus of research, to explore its abilities towards the electrochemical sensing of target molecules. For an effective and sensitive sensing of a target molecule, Co3O4 with different morphologies was synthesized by a facile single-step hydrothermal method. The higher electrocatalytic performance was observed by Co3O4 nanocubes with low limit of detection i.e. 0.93 M with the sensitivity value of 0.0485 ± 0.00063 μA.μM-1 for the detection of 4-nitrophenol. 4-NP is an important toxic phenol-based nitro-compound that can be found in the waste-water released by the chemical and pharmaceutical industries. The Co3O4 with cubical morphology was selected as a model nanostructure due to its higher catalytic performance and Co3O4 based nanocomposites were synthesized for further studies. Graphene, a two-dimensional allotrope of carbon with 2D honeycomb crystal lattice, having single atom thickness, large theoretical surface area with high conductivity at room temperature and wide electrochemical window, has attracted much attention by many researchers, was used as a conducting platform for Co3O4 nanocubes enrichment and to facilitate the electron transfer process. A Co3O4 based nanocomposite with different wt. % (2,4,8 and 12 wt.%) of graphene oxide (GO) was synthesized by the hydrothermal method and named as rGO-Co3O4 nanocomposite. The rGO-Co3O4 nanocomposite was used for the sensitive and selective detection of biological molecule serotonin (5-HT) a monoamine, present in enterochromaffin cells located in the colonic mucosal epithelium widely distributed in the central nervous system. The rGO-Co3O4-4 % nanocomposite has shown higher current value of 36 A with a lower potential value of 0.31 V. the limit of detection was found to be 1.128 M. It is known that transition metals have high catalytic activity, high conductivity and ability to sense the target molecules. Hence, the deposition of a minimal amount of metal nanoparticle was proven to be an electrochemical signal enhancer in sensor application. Therefore, a nanocomposite consists of reduced graphene oxide, cobalt oxide and gold nanoparticle (rGO-Co3O4@Au) was synthesized by the same single-step hydrothermal method and utilized for the detection of hydrazine, a toxic, colorless and flammable molecule. Higher electrocatalytic performance was observed with a low limit of detection i.e. 0.443 M for Hydrazine detection. Platinum (Pt) is considered a promising sensing element, due to its conducting nature and large surface area which boosts the electrochemical signal of the target analyte. Therefore, Co3O4 nanocubes deposited with Pt nanoparticle incorporated with graphene into a nanocomposite (rGO-Co3O4@Pt) was prepared by hydrothermal reaction and used as a sensor for the detection of nitric oxide (NO), a very important biological molecule responsible for vasodilation and blood pressure regulation in the nervous and cardiovascular systems of mammalian physiology. A limit of detection of 1.73 M was calculated with a sensitivity value of 0.58304 A.M-1. It will be worth mentioning that all the nanocomposites were synthesized for the first time by single step hydrothermal technique.